Development of Aurantiochytrium limacinum SR21 cultivation using salt-rich waste feedstock for docosahexaenoic acid production and application of natural colourant in food product. (January 2019) - Leong, Hui Yi; Su, Chien-An; Lee, Bo-Sheng; Lan, John Chi-Wei; Law, Chung Lim; Chang, Jo-Shu; Show, Pau Loke
Graphical abstract: Highlights: K2 HPO4 -waste feedstock is a potential replacement for KH2 PO4 in the cultivation. The waste feedstock with working concentration of 0.005% (w/v) showed optimal results. Higher productions of lipid (8.29%) and DHA (128.81 mg.L −1 ) content were noted. Reduction in the cost of microalgal cultivation. Utilisation of natural colouring agents for hard candy production. Abstract: Microalgae biorefinery is presently receiving a lot of attention as driven by its production of high value-added products. In this study, an oleaginous microalga Aurantiochytrium limacinum SR21 was cultured for docosahexaenoic acid (DHA) production using 20% (w/v) of K2 HPO4 -waste feedstock to replace 0.005% (w/v) of KH2 PO4 in the flask culture. DHA is an essential nutrient for human's brain functionalities. Collectively, the K2 HPO4 -waste feedstock with working concentration of 0.005% (w/v) in the cultivation prompted a higher lipid content (8.29%) and DHA production (128.81 mg.L −1 ). Moreover, natural plant pigment products containing stabilised betacyanins were utilised as natural red colourants for hard candy production. This study develops microalgal cultivation using salt-rich waste feedstock for a higher lipid and DHA content as well as application of natural colouring agents in food products.